Investigation of shock wave therapy dosages in the treatment of spasticity: An experimental study (Research, Society and Development, 2021)
The different functions of the shock waves regarding dose, intensity, application time and selection of suitable patients are analyzed, that is, the indications, contraindications and their complications. It is necessary to improve methods of applying shock waves in spasticity in a safe and coherent way, 23 cases, aged between 20 and 76 years, are selected. Divided into two different groups. Group 1: Composed of 10 normal individuals, high dosages are used. Dose: 0.050mj/mm² to 0.060mj/mm². Group 2: Composed of 13 individuals with spasticity, the same high dosages of the first group are used to check the skin's resistance to the dosage. The measurements compared the moments before and after applications using the modified Ashworth scale, digital goniometry, accelerometer and skin inspection to check for signs of bruises or petechiae. When analyzing the average, before the applications, the degree of elbow flexion was (37.2) and after the applications, the elbow flexion evolved to (61.0), making the elbow freer and more malleable. The second joint that showed improvement was shoulder abduction. The abduction that presented (40.2) started to present (49.6) degrees. Maximum acceleration improved comparing moments before and after shock wave applications (0.97-1.27). Petechiae, erythema and bruises are not observed in front of the equipment. At the end, a table with dosages and cycles and safe energy is shown. Conclusion: There was a decrease in spasticity in all assessments. The tolerance of patients to the equipment was satisfactorily observed in this study.